MODERNISASI DALAM PENDIDIKAN - Syamsul Aripin (Kopertais Wilayah I DKI Jakarta dan Banten, 2022)
Modernization that is happening today has brought changes to various aspects of life areas including education. The modernization of education occurred in the 19th century which was driven by the ruling elite who wanted Muslims not to be left behind by western nations by learning and adopting western progress, while modernization in Indonesia occurred in the 20th century which originated from the colonizers which was realized by establishing modern schools by struggle organizations led by reform figures. In the modern era, Islamic religious education and Islamic educational institutions are required to be professional, because society has undergone changes by prioritizing rationality. Efforts to reconcile religious teachings and the modern era continue to be made by Muslims to show that Islam is appropriate and does not conflict with the modern era. In the modern era, human life will be characterized by two tendencies that contradict each other/oppose Islam. Advances in science and technology (science and technology) bring positive and negative influences to human life, both of which are opposed to each other so that what is needed now is whether Islamic religious education is able to overcome and dialogue. This article will discuss modernization in education along with examples in an effort to become a quality school.